EFFICIENCY OF USING RESOURCE-SAVING AGROTECHNOLOGY IN MELON CULTIVATION - Ballasov Abdulhamid Ruzimahammad ugli; Yunusov Salohiddin Adhamovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This article describes agrotechnological methods aimed at saving water and fuel through resource-efficient cultivation of muskmelon (a type of melon) in open fields using transplant seedlings. The results showed that planting 20-day-old seedlings led to earlier ripening and had a positive effect on the growth and development of the above-ground parts of the plant. Among the studied varieties, Obi Novvot, Samarkand Yellow Muskmelon, and Local Yellow Muskmelon demonstrated the most vigorous growth in terms of the above-ground plant parts, including main stem length, number of lateral branches, total vine length, and number of leaves.